Cytotoxicity and Antimicrobial Activity of Propolis from Trigona itama Stingless Bees against Staphylococcus aureus and Escherichia coli - Yusop, Syed A. T. W.; Asaruddin, Mohd R.; Sukairi, Ahmad H.; Sabri, Wan M. A. W. (Indonesian Journal of Pharmaceutical Science and Technology, 2018)
Trigona itama is a stingless bees that produce honey which has been used widely as a traditional medicine. Due to limited research and knowledge on T. itama propolis, it becomes less popular in industrial production than honeybee propolis. The aim of this study was to identify the antibacterial activity and toxicity level in hexane, ethyl acetate and methanol extracts of T.itama propolis. T.itama propolis crude extract was tested for antibacterial activity by using disk di usion method. The antibacterial activities were assessed according to the inhibitory zone of agar medium with sample concentration of 1000 Î¼g/mL, 750 Î¼g/mL and 500 Î¼g/mL. The result from this study revealed that all T. itama propolis crude extract shows presence of inhibition zone against Staphylococcus aureus ATCC 25923 and Escherichia coli ATCC 25922. The brine shrimp lethality test was used to monitor the toxicity level of T. itama propolis where methanol, ethyl acetate and hexane fraction showed low activity of toxicity where all crude extract LC50 showed above 250 Î¼g/mL. It could be concluded from this study that extract from T. itama propolis possessed antimicrobial activity and low level of toxicity. Key Words: Escherichia coli, propolis, stingless bees, Staphylococcus aureus, Trigona itama